Preparation Of Cellulose Acetate Dialysis Membrane For Separation Of Bovine Serum Albumin - Idris, Ani; K.Y, Lee; H. K., Hing (Penerbit UTM Press, 2005)

(untitled)
Flat Sheet Dialysis Membranes Were Casted Using Phase Inversion Method, Using Cellulose Acetate As The Polymer And Acetic Acid As The Solvent. Modification Agents Such As Polyethylene Glycol 400 (PEG 400) And Non-Solvent Swelling Agent, I.E. Distillated Water Were Added. Three Different Formulations Were Used, And The Performances Of The Obtained Membranes Were Tested For Protein Separation Using A 2 Mg/Ml Bovine Serum Albumin (BSA) Solution. It Was Found That The Membrane Obtained From The Formulation Consisting Of 20%Wt Cellulose Acetate, 60%Wt Acetic Acid, 10%Wt PEG 400 And 10%Wt Distillated Water Gives A BSA Rejection Rate As High As 96.19%, Which Seems To Be Comparable With The Commercial Cellulose Acetate Dialysis Membranes. However, Testing The Same Membranes For Separation Of Sucrose Solution Does Not Give Satisfactory Result As Indicated By The Low Rejection Rates Of 50%.